2007
DOI: 10.4321/s0213-61632007000200006
|View full text |Cite
|
Sign up to set email alerts
|

A brief community linkage intervention for veterans with a persistent mental illness and a co-occurring substance abuse disorder

Abstract: -Objective: Individuals with co-occurring psychiatric and substance abuse problems often exhibit poor outpatient treatment engagement and re-hospitalization following discharge from acute psychiatric services. Although case management can improve treatment engagement and reduce attrition, these services are often delivered indefinitely, limiting the availability of treatment slots. In an effort to reduce re-hospitalization rates and improve outcomes during the transition from inpatient to outpatient treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…MISSION-CJ was adapted from our wraparound approach called MISSION, originally developed to help clients with a co-occurring mental health and substance abuse problem engage in community supports while simultaneously addressing some of their clinical needs, and has recently been included in the Substance Use and Mental Health Services National Registry for Evidence Based Practices (Smelson et al 2007;MISSION 2016). Our previous research has shown MISSION to improve mental health, substance use, housing, and employment outcomes for homeless clients as well as veterans (Smelson et al 2012(Smelson et al , 2013(Smelson et al , 2015.…”
Section: Mission-cj Model Developmentmentioning
confidence: 99%
“…MISSION-CJ was adapted from our wraparound approach called MISSION, originally developed to help clients with a co-occurring mental health and substance abuse problem engage in community supports while simultaneously addressing some of their clinical needs, and has recently been included in the Substance Use and Mental Health Services National Registry for Evidence Based Practices (Smelson et al 2007;MISSION 2016). Our previous research has shown MISSION to improve mental health, substance use, housing, and employment outcomes for homeless clients as well as veterans (Smelson et al 2012(Smelson et al , 2013(Smelson et al , 2015.…”
Section: Mission-cj Model Developmentmentioning
confidence: 99%
“…MISSION‐CJ grew out of our previously developed time‐limited, case management approach called MISSION‐VET, which was designed to meet the diverse needs of homeless veterans with CODs (Smelson, Sawh, Kane, et al, ; Smelson, Sawh, Rodrigues, et al, ). Our previous research on MISSION‐VET suggested that it was effective in improving substance use, housing, and employment outcomes for veterans (Smelson et al, , , , ). Therefore, MISSION‐VET provided an optimal starting point to facilitate the development of an integrated second‐generation, veteran‐centric, criminal justice intervention for justice‐involved veterans as it had many of the same treatment key components to address the offender population with co‐occurring disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Maintaining Independence and Sobriety Through Systems Integration, Outreach, and Networking (MISSION) is a 12-month wraparound program developed for veterans with co-occurring disorders. It consists of Dual Recovery Therapy, a manualized treatment for co-occurring disorders that includes elements of relapse prevention, social skills training, 12-step programs, and MET; Critical Time Intervention; and peer support (Smelson et al, 2007). MISSION is delivered by a case manager and peer specialist and is designed to support veterans as they transition from residential to outpatient care (Smelson et al, 2013).…”
Section: Maintaining Independence and Sobriety Through Systems Integr...mentioning
confidence: 99%